Evaluation of physical activity before and after respiratory rehabilitation in normal weight individuals with asthma: a feasibility study - Oliva, Federico Mattia; Tarasconi, Matteo; Malovini, Alberto; Zappa, Martina; Visca, Dina; Zampogna, Elisabetta (Frontiers in Sports and Active Living, 2024)
Background: Individuals with asthma spend less time engaging in physical activity compared to the general population. Increasing physical activity has become a patient-centered goal for the treatment of treatable traits of subjects with asthma. There are data showing the possible effects of a pulmonary rehabilitation program on physical activity in obese subjects with asthma but no in normal-weight asthmatics. The objective of this feasibility study is to estimate the number of daily steps and time spent on activity in normal-weight subjects with asthma, measured before and after a pulmonary rehabilitation program.Methods: normal weight subjects with moderate-severe asthma were evaluated. The subjects measured their daily steps with an accelerometer for 5 days before and after a pulmonary rehabilitation program. The study was registered on ClinicalTrials.gov: NCT05486689.Results: 17 subjects were enrolled, one drop-out and data on the time in activity of 2 subjects are missing due to a software error during the download. Data from 16 patients were analyzed. The median number of steps/day at baseline was 5578 (25th, 75th percentiles = 4874, 9685) while the median activity time was 214 (25th, 75th percentiles = 165, 239) minutes. After the rehabilitation the number of daily steps increased by a median value of 472 (p-value=0.561) and the time in activity reduced by 17 min (p-value=0.357). We also found a significant difference in quality of life, muscle strength and exercise capacity.Conclusions: the results of this study make it possible to calculate the sample size of future studies whose main outcome is daily steps in normal-weight subjects with asthma. The difficulties encountered in downloading time in activity data do not allow the same for this outcome.